Identification of subgroups of early-stage mycosis fungoides patients with increased itch and impaired quality of life - Nenonen, Julia; Winther, Anna H.; Jonsson, Pontus; Ivert, Lina U.; Brauner, Hanna (Frontiers in Oncology, 2025)
IntroductionMycosis fungoides (MF), Sézary syndrome (SS) and other cutaneous T-cell lymphomas (CTCLs) can have a severe impact on quality of life (QoL) and itch, but early MF is insufficiently investigated despite representing most patients. This single center study investigated associations between QoL/itch/depressive symptoms and clinical phenotypes in patients with CTCL with particular focus on early MF-stages.MethodsPatients were included during routine dermatological care. The primary outcomes included Dermatology Life Quality Index (DLQI), EuroQoL 5D (EQ-5D) index, Montgomery-Åsberg Depression Rating Scale – Self report (MADRS-S), and itch measured with a visual analogue scale (VAS-itch).ResultsIn the total CTCL cohort (n=76), median EQ-5D index was impaired in female vs male patients (0.73 vs 0.85, p = 0.040). Among early MF patients (n=58), increased disease activity correlated with impaired DLQI (r = 0.413, p = 0.0014) and EQ-5D index (r = -0.317, p = 0.0161). Early MF patients with plaques vs only patches reported impaired EQ-5D index (median 0.725 vs 0.848, p = 0.0032) and increased itch (median VAS 3.27 vs 0.43, p = 0.0006). MF patients with stage IB vs IA reported impaired DLQI (median 5.00 vs 1.00, p = 0.0006), impaired EQ-5D index (median 0.725 vs 0.848, p = 0.0040) and increased itch (median VAS 3.37 vs 0.54, p = 0.0487).DiscussionAlthough early MF patients reported generally a mild impact on QoL, this study highlights the need for disease management optimization for subgroups of early MF patients, including those with plaques, stage IB and higher disease activity.